SIMULATION AND ACCURACY VERIFICATION OF HIGH PRECISION GEAR HOBBING BASED ON CATIA - HE ZhongYuan; WANG ZhongHou; LIU Lei; WU ShiQing (Jixie qiangdu)
The existing gear hobbing simulation methods are difficult to follow the actual processing parameters, and the model obtained by the simulation does not measure the accuracy of the tooth surface. Therefore, they cannot provide effective guidance for the actual gear hobbing. Therefore, a high-precision gear hobbing is proposed. Simulation and accuracy verification methods. This method is based on the CATIA design platform, combined with the secondary development functions through commands such as translation, rotation, and Boolean operations in CATIA. After extracting the preliminary cogging model containing the main motion and the generated motion characteristics, the preliminary cogging model and the tooth blank are processed The simulation cutting of vertical feed motion completes high-precision gear hobbing simulation. The accuracy of the simulation model tooth surface was measured by establishing a standard tooth surface point set, and the error distribution of the simulation tooth surface was obtained, and the highest tooth surface accuracy error in the obtained simulation model was below 1 μm, which verified the correctness of the gear hobbing simulation method in this paper And simulation model accuracy.